User-Generated Content & Data - Georg Widschwendter (Marketing Review St.Gallen, 2016)
Balancing efficiency and effectives in one-to-one marketing is complex but achievable with the right audience-targeting data capabilities and scalable personalised messaging. While advertisers face headwinds with industry limitations, new solutions are emerging.
Keywords: 650